A Study of Code-Switching and Code-Mixing in Arabic Speaking Course - Muflihah Mufilhah (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2015)
Code switching is the process of code translation from a first language to a second language. While the code mixing is the process of inserting a second language during communication. Both of them frequently happen in education as one example in the Arabic teaching. It aims to give an understanding to students about the material presented. Therefore, the author tries to analyze about code switching and code mixing of Arabic in learning speaking skills. Related issues that need to be investigated are 1) forms of code switching and code mixing; 2) factors affecting the code switching and code mixing. Based on the analysis of data, the author found one type of code switching and code mixing and four causes of code switching and two causes of code mixing. Two types mentioned above are external code switching and external code mixing. As for the causes of code switching are factors such needs, speaker, listener and strengthening while the causes of code mixing are language and attitude.